Evaluasi Kebijakan Dinas Sosial Dalam Penanganan Gelandangan Dan Pengemis Kota Batam - Ayu wulandari (Dialektika Publik, 2023)
Homeless people and beggars on the streets are troubling the people of Batam City. In addition, it also violates the public order of Batam City because Batam is a homeless and beggar-free area. Homeless and beggars are often found at red lights and the control of homeless people has been carried out by the Batam city government. The control was carried out through the Batam City Social and Community Empowerment Service or known as UPTD Nilam Suri, but there were still homeless people roaming around. The purpose of this study is to analyze the evaluation of social service policies in dealing with homeless people and beggars as well as the factors that become obstacles to policy evaluation. This research needs to be carried out so that the Batam City government provides a new breakthrough to overcome the problem of homeless people and beggars who still roam the streets and provide a deterrent effect. This aims to make Batam City free of homeless people and beggars. The type of research used is descriptive qualitative, to provide an understanding of the problem under study. The results of the study show that the Policy Evaluation of the Social Service in dealing with homeless and beggars in Batam City has been going well but not optimal. This is due to budget constraints so that the number of human resources or HR qualifications, and supervision is inadequate.